BRIDGING FAITH AND PRAXIS: Everyday Theology and the Cultural Mandate in Post-Suramadu Madura - Ana Budi Kristiani; Njoo Tomas Wibowo; Vian Klasia Wenno; Isak Suria; Beanto Benny (QUAERENS: Journal of Theology and Christianity Studies, 2025)
This study examines the role of everyday theology in relation to the cultural mandate and its practical implementation in post-Suramadu Madura. Employing a descriptive qualitative approach, data were collected through questionnaires distributed to five churches. The findings indicate that while theological understanding of culture (100%), creation (80%), and economy (80%) is relatively strong, its practical implementation across key sectors remains limited, including agriculture (20%), livestock (0%), tourism (20%), education (20%), and healthcare (40%). These results reveal a significant gap between theological understanding and ecclesial praxis. This study argues that everyday theology can function as a praxis-oriented framework that enables churches to engage more contextually and holistically with socio-economic realities. It contributes to practical theology by demonstrating how everyday theology bridges the gap between theological reflection and lived practice in the post-Suramadu Madurese context.